Dynamic Performance Analysis of Conventional Power Systems Incorporating EHVAC/HVDC Links - Ram Naresh Mishra (International Journal of Advanced Science and Technology, 2020)
This article presents a comparative study of the dynamic performances of thermal-thermal and hydrothermal energy systems when they are subjected to load disturbances of 1%. For these power systems, the interconnection is only considered as the EHVAC link, only the HVDC and EHVAC link in parallel with the HVDC link. The dynamic model of the incremental power flow across the HVDC link is based solely on the frequency difference at the end of the rectifier. The HVDC link is considered to operate in constant current control mode. To carry out the research, optimal controllers for AGC are designed using a more comprehensive proportional-integral control strategy. System responses are simulated using Matlab. In addition, to study the stability of the closed loop system, the eigenvalues ​​are calculated.